Platinum-gold sulfidation high-temperature-resistant high-flame-retardant silicone rubber and preparation method thereof
Patent Information
- Application Number
- CN202611401308.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-10
- Publication Date
- 2026-10-27
AI Technical Summary
[0006]为了现有铂金加成型硅橡胶无法在保持其洁净透明、无异味、高弹性固有优势的同时,兼顾220℃以上长期热氧老化环境下的交联网络稳定性、持久阻燃性及外观无黄变性的问题,本申请提供一种铂金硫化高耐温高阻燃硅橡胶及其制备方法
1、耐高温热氧老化:纳米氧化铈、氧化铁和氧化锆组成的复合耐高温稳定剂形成多重抗氧化屏障,配合优化的交联体系与二段高温定型工艺,使硅橡胶在220℃以上长期热氧老化下保持交联网络稳定、力学性能不衰减且外观无黄变。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This application relates to the field of silicone rubber processing technology, and more specifically, to a platinum vulcanized high-temperature resistant and high-flame-retardant silicone rubber and its preparation method. Background Technology
[0002] Silicone rubber, a polymeric elastomer with a main chain composed of silicon-oxygen bonds, possesses excellent high and low temperature resistance, weather resistance, electrical insulation, and physiological inertness, leading to its widespread application in high-end equipment sealing, thermal management of new energy vehicles, aerospace, medical devices, and food contact materials. Platinum addition-cured silicone rubber, based on vinyl-containing polysiloxanes as the base polymer and hydrogen-containing silicone oil as the crosslinking agent, achieves crosslinking and curing through a hydrosilylation reaction under the action of a platinum-based catalyst. Compared to traditional peroxide curing systems, the platinum addition-curing process does not produce small-molecule byproducts and offers significant advantages such as odorless precipitation, uniform curing, low linear shrinkage, transparent and clean products, and high elasticity retention. Therefore, it has become the preferred material for applications with stringent requirements for cleanliness, appearance, and mechanical stability.
[0003] However, the long-term safe operating temperature of existing platinum-cured silicone rubber is typically only 180–200°C. When the ambient temperature rises above 220°C and is accompanied by long-term thermo-oxidative aging, the silicon-oxygen backbone undergoes random fracture under high temperature and reactive oxygen free radical attack, and the cross-linked network structure rapidly disintegrates. This manifests as a sharp decline in tensile and tear strength, surface cracking and powdering, a significant decrease in volume resistivity, and insulation failure. These performance degradations make ordinary platinum-cured silicone rubber unsuitable for extreme operating conditions such as thermal runaway protection of new energy vehicle battery packs, high-temperature radiation in aircraft engine compartments, and heat dissipation of high-power devices in 5G base stations.
[0004] To improve the flame retardant properties of silicone rubber, a common approach is to fill the matrix with large amounts of inorganic flame retardant powders such as aluminum hydroxide, magnesium hydroxide, and zinc borate. However, this method has significant technical problems: while the introduction of a large proportion of inorganic powders can improve the flame retardant rating to some extent, it severely damages the integrity of the continuous cross-linked phase of the silicone rubber. The accumulation of a large number of powder particles in the polymer matrix not only hinders the uniform dispersion and effective contact of the platinum catalytic system, leading to uneven cross-linking density, poor vulcanization, or even localized under-vulcanization, but also causes stress concentration under high-temperature service conditions due to the mismatch in the thermal expansion coefficients of the powder-polymer interface, accelerating interface debonding and crack propagation. More importantly, conventional flame retardant powders are prone to sintering, pulverizing, and migrating at high temperatures, leading to the gradual failure of the flame retardant system; simultaneously, metal ion impurities on the powder surface easily catalyze the degradation of the silicon-oxygen backbone in a high-temperature, thermo-oxidative environment, causing yellowing, discoloration, and a precipitous decline in mechanical properties of the product. The aforementioned defects mean that conventional high flame retardant formulations cannot meet the comprehensive requirements of high-end equipment, medical devices, and food-grade applications for clean flame retardancy, high-temperature aging resistance, and appearance stability.
[0005] In summary, how to maintain the inherent advantages of platinum addition-cured silicone rubber, such as cleanliness, transparency, low shrinkage, and high elasticity, while simultaneously ensuring the stable maintenance of the crosslinking network, the long-lasting and effective flame retardant properties, and the absence of yellowing in the long-term thermo-oxidative aging environment above 220°C, has become an urgent problem to be solved in this field. Summary of the Invention
[0006] To address the issue that existing platinum addition-cured silicone rubbers cannot maintain their inherent advantages of cleanliness, transparency, odorlessness, and high elasticity while also ensuring crosslinking network stability, long-lasting flame retardancy, and non-yellowing appearance under long-term thermo-oxidative aging conditions above 220°C, this application provides a platinum vulcanized high-temperature resistant and high-flame-retardant silicone rubber and its preparation method.
[0007] In a first aspect, this application provides a platinum-cured high-temperature-resistant and high-flame-retardant silicone rubber, employing the following technical solution: A platinum-cured high-temperature resistant and high-flame-retardant silicone rubber is prepared from the following raw materials in parts by weight: 100 parts of methyl vinyl silicone rubber raw material 6-10 parts of hydroxyl silicone oil 5-8 parts of structure control agent 30-50 parts of highly hydrophobic modified fumed silica 60-70 parts of halogen-free flame retardant filler 3-7 parts of composite high temperature stabilizer 2-4 parts of hydrogen-containing crosslinking agent 0.5-1 part platinum vulcanizing agent Inhibitor 0.2-0.4 parts 1-2 parts of silane interface compatibilizer; The composite high-temperature stabilizer is composed of nano-cerium oxide, nano-iron oxide, and nano-zirconia.
[0008] Preferably, the weight ratio of the nano-cerium oxide, the nano-iron oxide, and the nano-zirconia is 10:2-4:1.
[0009] By adopting the above technical solution, while maintaining the inherent advantages of platinum addition-cured silicone rubber such as cleanliness, transparency, odorlessness, low shrinkage, and high elasticity, a comprehensive technical effect is achieved, including stable maintenance of the crosslinking network, long-lasting and effective flame retardant properties, and no yellowing of the appearance, under long-term thermo-oxidative aging conditions above 220°C.
[0010] Among them, silane interface compatibilizers perform surface functionalization modification on halogen-free flame-retardant fillers, improving their interfacial compatibility with the silicone rubber matrix. This not only alleviates the problems of interfacial debonding and stress concentration caused by the mismatch of thermal expansion coefficients under high-temperature service, but also effectively inhibits the sintering, pulverization, detachment, and migration of flame-retardant powders at high temperatures, as well as the catalytic degradation of the silicon-oxygen backbone by surface metal ion impurities, enabling the flame-retardant system to maintain stable performance during high-temperature aging. The composite high-temperature stabilizer, consisting of nano-cerium oxide, nano-iron oxide, and nano-zirconia, forms a multi-component synergistic stabilizing system. Nano-cerium oxide preferentially captures reactive oxygen free radicals in the high-temperature thermo-oxidative environment, blocking the random breakage reaction of the silicon-oxygen backbone. Nano-iron oxide and nano-zirconia further synergistically stabilize the cross-linked network structure and inhibit high-temperature yellowing. The three components work together to provide multiple protective barriers for silicone rubber under long-term thermo-oxidative aging conditions above 220℃. The hydrogen cross-linking agent and platinum vulcanizing agent, under inhibitor regulation, achieve uniform and controllable hydrosilylation reactions, ensuring no small molecule byproduct precipitation and maintaining low shrinkage and high elasticity of the product. The synergistic effect of hydroxyl silicone oil and structure control agent effectively suppresses the structuring tendency of highly hydrophobic modified fumed silica in methyl vinyl silicone rubber raw rubber, ensuring that the reinforcing network is uniformly dispersed and does not interfere with the catalytic activity of platinum vulcanizing agent, thereby ensuring uniform vulcanization crosslinking density and transparent and clean products.
[0011] Preferably, the halogen-free flame retardant filler is composed of modified aluminum hydroxide, zinc-free flame retardant powder and modified silica powder in a weight ratio of 6-7:2-4:1.
[0012] Preferably, the zinc-free flame-retardant powder comprises at least one of hydrotalcite, ammonium polyphosphate, melamine polyphosphate, silicate, and montmorillonite.
[0013] By adopting the above technical solution, modified aluminum hydroxide, as the main flame-retardant component, releases crystal water through endothermic decomposition at high temperatures to dilute combustible gases and form a dense oxide heat-insulating layer, playing a major flame-retardant role. Zinc-free flame-retardant powder synergistically enhances the effect, promoting char formation and inhibiting dripping while avoiding the high-temperature catalytic degradation of the silicon-oxygen backbone by zinc ions, thus improving the long-term stability of the flame-retardant system. Modified silica powder improves the interfacial compatibility between the filler and the silicone rubber matrix through surface functionalization, effectively alleviating interfacial debonding and stress concentration caused by differences in thermal expansion coefficients under high-temperature service, while also inhibiting powder sintering, pulverization, and migration. The three components are compounded in a weight ratio of 6-7:2-4:1, ensuring a high flame-retardant rating while minimizing damage to the continuous phase of platinum vulcanization crosslinking, ensuring the long-lasting and effective flame-retardant performance of silicone rubber under long-term thermo-oxidative aging conditions above 220℃, maintaining the stability of the crosslinking network, and preventing yellowing.
[0014] Preferably, the modified aluminum hydroxide is prepared by the following method: 1) Mix aluminum hydroxide and 3,4-dihydroxybenzoic acid solution, grind, and filter to obtain activated aluminum hydroxide; 2) Dissolve hexachlorocyclotriphosphazene in petroleum ether to obtain an epoxy phosphate-petroleum ether solution. Then, under stirring conditions, add active aluminum hydroxide to the epoxy phosphate-petroleum ether solution, heat to 55-70℃, add triethylamine dropwise, react for 0.5-2 hours, filter to obtain filter cake, wash and dry to obtain modified aluminum hydroxide.
[0015] Preferably, the ratio of the aluminum hydroxide, the 3,4-dihydroxybenzoic acid solution, the hexachlorocyclotriphosphazene, the petroleum ether, and the triethylamine is 10-15g:10-20ml:4-5-5g:60-80ml:1g.
[0016] By employing the above technical solution, aluminum hydroxide is pretreated with 3,4-dihydroxybenzoic acid to activate the surface, introducing phenolic hydroxyl and carboxyl active sites, thereby enhancing the reactivity of the aluminum hydroxide surface. Subsequently, using hexachlorocyclotriphosphazene as a modifier, phosphorus- and nitrogen-containing phosphazene ring structures are chemically grafted onto the aluminum hydroxide surface under triethylamine catalysis. This not only endows it with a PN synergistic flame retardant effect, significantly improving the flame retardant efficiency, but also reduces the polarity of the filler through surface organic modification, improving the interfacial compatibility and dispersion uniformity with the silicone rubber matrix. At the same time, the chemically bonded organic coating layer effectively isolates the catalytic degradation of the silicon-oxygen backbone by metal ion impurities on the aluminum hydroxide surface at high temperatures, inhibits yellowing of the product, and prevents the sintering, pulverization, and migration of flame retardant components during high-temperature service, ensuring the long-term stability of flame retardant performance under long-term thermo-oxidative aging conditions above 220°C.
[0017] Preferably, the modified silicon powder is obtained by mixing silicon powder and mercaptosilane coupling agent in a weight ratio of 10:0.5-1.
[0018] By adopting the above technical solution, mercaptosilane coupling agent organically modifies the surface of silicon micropowder, improves its interfacial compatibility and dispersion uniformity with the silicone rubber matrix, enhances the interfacial bonding force of filler-polymer, and effectively alleviates interfacial debonding and stress concentration caused by thermal expansion coefficient mismatch under high-temperature service. At the same time, the organic coating layer effectively isolates surface metal ion impurities, inhibits the sintering, pulverization, and migration of silicon micropowder at high temperatures, avoids catalytic degradation of the silicon-oxygen backbone, and ensures that the flame retardant system can play a long-term and stable role in the long-term thermo-oxidative aging environment above 220°C.
[0019] Preferably, the hydrogen-containing crosslinking agent is composed of a side-chain type hydrogen-containing silicone oil with a hydrogen content of 0.3%-0.75% and a methyl low-hydrogen silicone oil with a hydrogen content of 0.5%-1.0% in a weight ratio of 3:0.5-1.5.
[0020] By adopting the above technical solution, side-chain hydrogen-containing silicone oil provides crosslinking sites, and methyl low-hydrogen silicone oil adjusts the crosslinking density. The combination of the two makes the hydrosilylation uniform and controllable, forming a dense and flexible crosslinking network, ensuring no small molecule by-products are precipitated, giving the product high elasticity, low shrinkage and excellent mechanical stability, and resistance to long-term thermo-oxidative aging above 220°C.
[0021] Preferably, the structure control agent includes at least one of diphenylsilanediol, dimethyldimethoxysilane, methylphenyldimethoxysilane, and hexamethyldisilazane.
[0022] By adopting the above technical solutions, the tendency of silica to structurate in silicone rubber raw rubber is effectively suppressed, preventing the rubber from hardening and reducing its plasticity. This ensures that the reinforcing filler is evenly dispersed and does not interfere with the activity of the platinum catalytic system, thereby ensuring uniform vulcanization crosslinking density, good processing performance, and keeping the product transparent, clean, highly elastic, and with excellent mechanical stability.
[0023] Preferably, the methyl vinyl silicone rubber raw rubber has a vinyl content of 0.20%-0.30% and a molecular weight of 400,000-600,000.
[0024] By adopting the above technical solution, a vinyl content of 0.20%-0.30% provides an appropriate number of crosslinking sites, ensuring a moderate vulcanization crosslinking density while balancing high strength and high elasticity; a molecular weight of 400,000-600,000 ensures sufficient chain length, giving the matrix excellent mechanical strength, resilience, and tear resistance. The synergy of these two factors allows silicone rubber to maintain high elasticity while possessing good processability and mechanical stability.
[0025] Preferably, the silane interface compatibilizer includes at least one of vinyltrimethoxysilane, vinyltriethoxysilane, and vinyltri(2-methoxyethoxy)silane.
[0026] By adopting the above technical solutions, the dispersibility and interfacial bonding of fillers are improved, the debinding caused by high-temperature thermal expansion mismatch is alleviated, the sintering migration of powder and the catalytic degradation of metal ions are inhibited, and the flame retardant is ensured to be long-lasting and stable.
[0027] Secondly, this application provides a method for preparing platinum-cured high-temperature resistant and high-flame-retardant silicone rubber, using the following technical solution: A method for preparing platinum-cured high-temperature resistant and high-flame-retardant silicone rubber includes the following preparation steps: S1. Knead the raw methyl vinyl silicone rubber. During the kneading process, add highly hydrophobic modified fumed silica, silane interface compatibilizer, hydroxyl silicone oil and structure control agent in sequence. After the addition is completed, continue kneading for 180-200 min. Then add halogen-free flame retardant filler, composite high temperature resistant stabilizer and hydrogen-containing crosslinking agent. After the addition is completed, continue kneading for 45-60 min to obtain a mixture. S2. Reduce the temperature of the mixture to below 35°C, add the inhibitor first, then add the platinum vulcanizing agent, mix evenly, roll and pass through thin sheets, vulcanize, and obtain platinum vulcanized high temperature resistant and high flame retardant silicone rubber.
[0028] The vulcanization process is as follows: First-stage vulcanization: temperature 175-180℃, pressure 7-9MPa, time 10-12min; Two-stage high-temperature aging and setting: temperature is 190-210℃, time is 4-6 hours.
[0029] By adopting the above technical solution, after mixing, rolling, and thin-passing, a first-stage vulcanization is performed to achieve rapid and uniform cross-linking and shaping, followed by a second-stage high-temperature aging and shaping to further promote complete cross-linking reaction, remove residual low-molecular-weight substances, and stabilize the cross-linking network structure. The above processes synergistically ensure the uniform dispersion and interfacial bonding of each component in the silicone rubber matrix, so that the resulting product retains the inherent advantages of platinum addition-cure silicone rubber, such as cleanliness, transparency, odorlessness, low shrinkage, and high elasticity, while possessing cross-linking network stability, long-lasting flame retardancy, and no yellowing appearance under long-term thermo-oxidative aging conditions above 220°C.
[0030] In summary, this application has the following beneficial effects: 1. High temperature and oxidative aging resistance: The composite high temperature stabilizer composed of nano-cerium oxide, iron oxide and zirconium oxide forms multiple antioxidant barriers. Combined with the optimized crosslinking system and two-stage high temperature setting process, the silicone rubber maintains the stability of the crosslinking network, does not degrade its mechanical properties and does not yellow under long-term oxidative aging at temperatures above 220°C.
[0031] 2. Synergistic effect of flame retardancy and mechanical properties: Phosphazene-modified aluminum hydroxide, zinc-free flame retardant powder and mercapto-modified silica powder are uniformly dispersed under the bridging of silane compatibilizer. While achieving long-lasting and efficient flame retardancy, it avoids the damage to the platinum cross-linking network caused by high filling, and takes into account high elasticity, low shrinkage and excellent mechanical stability.
[0032] 3. Maintaining the advantages of cleanliness and transparency: Platinum addition-curing vulcanization produces no small molecule byproducts. Combined with structure control agents and step-by-step kneading processes, it ensures uniform vulcanization, transparent and clean rubber compound, and no odor, meeting the stringent cleanliness requirements of high-end equipment, new energy vehicles, and medical and food contact fields. Detailed Implementation Preparation Example
[0033] The 3,4-dihydroxybenzoic acid solution is prepared by dissolving 3,4-dihydroxybenzoic acid in diethyl ether, and its concentration is 1.5 g / 10 ml.
[0034] Preparation Example 1 A modified aluminum hydroxide is prepared by the following method: Mix 60g of aluminum hydroxide with 60ml of 3,4-dihydroxybenzoic acid solution, grind, and filter to obtain activated aluminum hydroxide. 2) Dissolve 24g of hexachlorocyclotriphosphazene in 360ml of petroleum ether to obtain an epoxy phosphate-petroleum ether solution. Then, under stirring, add active aluminum hydroxide to the epoxy phosphate-petroleum ether solution, heat to 55℃, add 6g of triethylamine dropwise, react for 2h, filter to obtain filter cake, wash and dry to obtain modified aluminum hydroxide.
[0035] Preparation Example 2 A modified aluminum hydroxide is prepared by the following method: 1) Mix 72g of aluminum hydroxide and 90ml of 3,4-dihydroxybenzoic acid solution, grind, and filter to obtain activated aluminum hydroxide; 2) Dissolve 25.8g of hexachlorocyclotriphosphazene in 420ml of petroleum ether to obtain an epoxy phosphate-petroleum ether solution. Then, under stirring, add active aluminum hydroxide to the epoxy phosphate-petroleum ether solution, heat to 65℃, add 6g of triethylamine dropwise, react for 1h, filter to obtain filter cake, wash and dry to obtain modified aluminum hydroxide.
[0036] Preparation Example 3 A modified aluminum hydroxide is prepared by the following method: 1) Mix 90g of aluminum hydroxide and 120ml of 3,4-dihydroxybenzoic acid solution, grind, and filter to obtain activated aluminum hydroxide; 2) Dissolve 30g of hexachlorocyclotriphosphazene in 480ml of petroleum ether to obtain an epoxy phosphate-petroleum ether solution. Then, under stirring conditions, add active aluminum hydroxide to the epoxy phosphate-petroleum ether solution, heat to 70℃, add 6g of triethylamine dropwise, react for 2h, filter to obtain filter cake, wash and dry to obtain modified aluminum hydroxide.
[0037] Preparation Example 4 A modified aluminum hydroxide, the difference between this preparation example and preparation example 1 is that 3,4-dihydroxybenzoic acid is replaced with diethyl ether.
[0038] Preparation Example 5 A modified aluminum hydroxide, the difference between this preparation example and preparation example 1 is that hexachlorocyclotriphosphazene is replaced with tributyl phosphate.
[0039] Example The hydroxyl silicone oil was selected from Jiangxi Lanxing Xinghuo Organosilicon Co., Ltd., with a viscosity of 350 cst and a hydroxyl value of 8%.
[0040] The molecular formula of hydrogen-containing silicone oil with side chains is (CH3)3SiO [(CH3)HSiO]. n [(CH3)2SiO]m Si(CH3)3, in which the Si-H bond is located on the side chain.
[0041] The molecular formula of methyl low-hydrogen silicone oil is: (CH3)3Si0[(CH3)(H)Si0]nSi(CH3)3.
[0042] Example 1 A platinum-cured high-temperature-resistant and high-flame-retardant silicone rubber is prepared by the following method: S1. Knead 100g of methyl vinyl silicone rubber raw rubber. During the kneading process, add 30g of highly hydrophobic modified fumed silica, 1g of silane interface compatibilizer (vinyltrimethoxysilane), 6g of hydroxyl silicone oil, and 5g of structure control agent (diphenylsilanediol) in sequence. After the addition is completed, continue kneading for 180min. Then add 60g of halogen-free flame retardant filler, 3g of composite high temperature resistant stabilizer, and 2g of hydrogen-containing crosslinking agent. After the addition is completed, continue kneading for 45min to obtain a mixture. The methyl vinyl silicone rubber raw material has a vinyl content of 0.30% and a molecular weight of 600,000. The composite high-temperature stabilizer is composed of nano-cerium oxide, nano-iron oxide and nano-zirconia in a weight ratio of 10:2:1; The halogen-free flame retardant filler is composed of modified aluminum hydroxide, zinc-free flame retardant powder (hydrotalcite), and modified silica powder in a weight ratio of 6:2:1. The modified silica powder is obtained by mixing silica powder and mercaptosilane coupling agent (3-mercaptopropyltrimethoxysilane) in a weight ratio of 10:0.5; The hydrogen-containing crosslinking agent is composed of a side-chain type hydrogen-containing silicone oil with a hydrogen content of 0.3% and a methyl low-hydrogen silicone oil with a hydrogen content of 0.5% in a weight ratio of 3:0.5. S2. Reduce the temperature of the mixture to below 35°C, add 0.2g of inhibitor (3-methyl-1-butyn-3-ol), then add 0.5g of platinum vulcanizing agent (Karstedt catalyst), mix evenly, roll and pass through thin sheets, vulcanize to obtain platinum vulcanized high temperature resistant and high flame retardant silicone rubber. The vulcanization process is as follows: First-stage vulcanization: temperature 175℃, pressure 7MPa, time 10min; Two-stage high-temperature aging and setting: temperature is 190℃, time is 4 hours.
[0043] Example 2 A platinum-cured high-temperature-resistant and high-flame-retardant silicone rubber is prepared by the following method: S1. Knead 100g of methyl vinyl silicone rubber raw rubber. During the kneading process, add 40g of highly hydrophobic modified fumed silica, 1.5g of silane interface compatibilizer (vinyltris(2-methoxyethoxy)silane), 8g of hydroxyl silicone oil, and 6.5g of structure control agent (dimethyldimethoxysilane) in sequence. After the addition is completed, continue kneading for 190min. Then add 65g of halogen-free flame retardant filler, 5g of composite high temperature resistant stabilizer, and 3g of hydrogen-containing crosslinking agent. After the addition is completed, continue kneading for 45min to obtain a mixture. The methyl vinyl silicone rubber raw material has a vinyl content of 0.25% and a molecular weight of 500,000; The composite high-temperature stabilizer is composed of nano-cerium oxide, nano-iron oxide and nano-zirconia in a weight ratio of 10:3:1; The halogen-free flame retardant filler is composed of modified aluminum hydroxide, zinc-free flame retardant powder (montmorillonite), and modified silica powder in a weight ratio of 6.5:3:1. The modified silica powder was obtained by mixing silica powder and mercaptosilane coupling agent (3-mercaptopropyltrimethoxysilane) in a weight ratio of 10:0.8. The hydrogen-containing crosslinking agent is composed of a side-chain type hydrogen-containing silicone oil with a hydrogen content of 0.5% and a methyl low-hydrogen silicone oil with a hydrogen content of 0.8% in a weight ratio of 3:1. S2. Reduce the temperature of the mixture to below 35°C, add 0.2g of inhibitor (3-methyl-1-butyn-3-ol), then add 0.5g of platinum vulcanizing agent (Karstedt catalyst), mix evenly, roll and pass through thin sheets, vulcanize to obtain platinum vulcanized high temperature resistant and high flame retardant silicone rubber. The vulcanization process is as follows: First-stage vulcanization: temperature 178℃, pressure 8MPa, time 11min; Two-stage high-temperature aging and setting: temperature is 200℃, time is 5h.
[0044] Example 3 A platinum-cured high-temperature-resistant and high-flame-retardant silicone rubber is prepared by the following method: S1. Knead 100g of methyl vinyl silicone rubber raw rubber. During the kneading process, add 50g of highly hydrophobic modified fumed silica, 2g of silane interface compatibilizer (vinyltriethoxysilane), 10g of hydroxyl silicone oil, and 8g of structure control agent (hexamethyldisilazane) in sequence. After the addition is completed, continue kneading for 200min. Then add 70g of halogen-free flame retardant filler, 7g of composite high temperature resistant stabilizer, and 4g of hydrogen-containing crosslinking agent. After the addition is completed, continue kneading for 60min to obtain a mixture. The methyl vinyl silicone rubber raw material has a vinyl content of 0.30% and a molecular weight of 400,000. The composite high-temperature stabilizer is composed of nano-cerium oxide, nano-iron oxide and nano-zirconia in a weight ratio of 10:4:1; The halogen-free flame retardant filler is composed of modified aluminum hydroxide, zinc-free flame retardant powder (ammonium polyphosphate), and modified silica powder in a weight ratio of 7:4:1. The modified silica powder was obtained by mixing silica powder and mercaptosilane coupling agent (3-mercaptopropyltrimethoxysilane) in a weight ratio of 10:1. The hydrogen-containing crosslinking agent is composed of a side-chain type hydrogen-containing silicone oil with a hydrogen content of 0.75% and a methyl low-hydrogen silicone oil with a hydrogen content of 1.0% in a weight ratio of 3:1.5. S2. Reduce the temperature of the mixture to below 35°C, add 0.4g of inhibitor (3-methyl-1-butyn-3-ol), then add 1g of platinum vulcanizing agent (Karstedt catalyst), mix evenly, roll and pass through thin sheets, vulcanize to obtain platinum vulcanized high temperature resistant and high flame retardant silicone rubber. The vulcanization process is as follows: First-stage vulcanization: temperature 180℃, pressure 9MPa, time 12min; Two-stage high-temperature aging and setting: temperature is 210℃, time is 6h.
[0045] Example 4 A platinum-cured high-temperature resistant and high-flame-retardant silicone rubber, the difference between this embodiment and Example 1 is that the composite high-temperature resistant stabilizer is composed of nano-cerium oxide, nano-iron oxide and nano-zirconia in a weight ratio of 4:4:1.
[0046] Example 5 A platinum-cured high-temperature-resistant and high-flame-retardant silicone rubber, the difference between this embodiment and embodiment 1 is that the halogen-free flame-retardant filler is composed of aluminum hydroxide, zinc-free flame-retardant powder (hydrotalcite) and modified silica powder in a weight ratio of 6:2:1.
[0047] Example 6 A platinum-cured high-temperature resistant and high-flame-retardant silicone rubber, the difference between this embodiment and Example 1 is that the modified aluminum hydroxide comes from Preparation Example 4.
[0048] Example 7 A platinum-cured high-temperature-resistant and high-flame-retardant silicone rubber, the difference between this embodiment and Example 1 is that the modified aluminum hydroxide is derived from Preparation Example 5.
[0049] Example 8 A platinum-cured high-temperature resistant and high-flame-retardant silicone rubber, the difference between this embodiment and Embodiment 1 is that the halogen-free flame-retardant filler is modified aluminum hydroxide.
[0050] Example 9 A platinum-cured high-temperature-resistant and high-flame-retardant silicone rubber, the difference between this embodiment and Example 1 is that the halogen flame-retardant filler is composed of modified aluminum hydroxide and modified silica powder in a weight ratio of 6:1.
[0051] Example 10 A platinum-cured high-temperature resistant and high-flame-retardant silicone rubber, the difference between this embodiment and Example 1 is that the hydrogen-containing crosslinking agent is a side-chain type hydrogen-containing silicone oil with a hydrogen content of 0.3%.
[0052] Comparative Example Comparative Example 1 A platinum-cured high-temperature-resistant and high-flame-retardant silicone rubber, the difference between this comparative example and Example 1 is that no composite high-temperature stabilizer is added.
[0053] Comparative Example 2 A platinum-cured high-temperature resistant and high-flame-retardant silicone rubber, the difference between this comparative example and Example 1 is that the composite high-temperature resistant stabilizer is composed of nano-cerium oxide and nano-zirconia in a weight ratio of 10:1.
[0054] Comparative Example 3 A platinum-cured high-temperature resistant and high-flame-retardant silicone rubber, the difference between this comparative example and Example 1 is that the composite high-temperature resistant stabilizer is nano-cerium oxide.
[0055] Detection methods / test methods Transmittance: The transmittance of the prepared platinum vulcanized high-temperature resistant and high-flame-retardant silicone rubber was measured at 450 nm using an ultraviolet spectrophotometer. Compression set: determined according to ISO 815-1; High temperature resistance: The silicone rubber sample was placed in an electric heating drying oven and aged at 250℃ for 500h, and then its light transmittance and compression set were tested. Oxygen index: tested according to ISO 4589-2; Flame retardancy rating: tested according to UL-94 standard; experimental data are shown in Table 1: Table 1. Experimental data of Examples 1-10 and Comparative Examples 1-3
[0056] As can be seen from the above experimental data, this application achieves a synergistic effect of high transparency, high elasticity, and long-lasting high-temperature flame retardancy by adding a composite high-temperature stabilizer composed of nano-cerium oxide, nano-iron oxide, and nano-zirconia in a specific weight ratio to methyl vinyl silicone rubber raw rubber, combined with a halogen-free flame retardant filler system consisting of aluminum hydroxide activated by 3,4-dihydroxybenzoic acid and modified with hexachlorocyclotriphosphazene, zinc-free flame retardant powder, and mercaptosilane-modified silica micropowder, as well as a crosslinking agent composed of side-chain hydrogen-containing silicone oil and methyl low-hydrogen-content silicone oil. This results in platinum vulcanized silicone rubber that maintains an initial light transmittance of 88%-92%, an oxygen index of 36.5%-38.0%, and UL-94 V-0 flame retardancy, while still maintaining a light transmittance of 78%-82% and a compression set of 24%-26% after 500 hours of thermo-oxidative aging at 250℃.
[0057] In contrast, Comparative Example 1, without the addition of the composite high-temperature stabilizer, showed a sharp drop in light transmittance to 35% and a compression set as high as 62% under the same aging conditions. Comparative Examples 2 and 3, which lacked nano-iron oxide or nano-zirconia respectively, also showed significant performance degradation. This indicates that the synergistic stabilization system of nano-cerium oxide, nano-iron oxide and nano-zirconia has a positive effect on long-term thermo-oxidative aging protection above 220℃.
[0058] Examples 4-10 demonstrate, through experiments involving deviations from the preferred stabilizer ratio, the use of unmodified aluminum hydroxide, a simplified flame-retardant filler compound system, or a single crosslinking agent, that only by adhering to the preferred ratio of the composite high-temperature resistant stabilizer, the phosphazene-modified aluminum hydroxide preparation process, the ternary compound system of halogen-free flame-retardant filler, and the synergistic effect of the compound crosslinking agent as defined in this application, can the inherent advantages of platinum vulcanized silicone rubber—cleanliness, transparency, odorlessness, low shrinkage, and high elasticity—be maintained, while also ensuring the stability of the crosslinking network, durable flame retardancy, and non-yellowing appearance under long-term thermo-oxidative aging conditions above 220°C.
[0059] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A platinum-cured high-temperature resistant and high-flame-retardant silicone rubber, characterized in that, It is prepared from the following raw materials in parts by weight: 100 parts of methyl vinyl silicone rubber raw material 6-10 parts of hydroxyl silicone oil 5-8 parts of structure control agent 30-50 parts of highly hydrophobic modified fumed silica 60-70 parts of halogen-free flame retardant filler 3-7 parts of composite high temperature stabilizer 2-4 parts of hydrogen-containing crosslinking agent 0.5-1 part platinum vulcanizing agent Inhibitor 0.2-0.4 parts 1-2 parts of silane interface compatibilizer; The composite high-temperature stabilizer is composed of nano-cerium oxide, nano-iron oxide, and nano-zirconia.
2. The platinum-cured high-temperature resistant and high-flame-retardant silicone rubber according to claim 1, characterized in that: The weight ratio of the nano-cerium oxide, the nano-iron oxide, and the nano-zirconia is 10:2-4:
1.
3. The platinum-cured high-temperature resistant and high-flame-retardant silicone rubber according to claim 1, characterized in that: The halogen-free flame retardant filler is composed of modified aluminum hydroxide, zinc-free flame retardant powder and modified silica powder in a weight ratio of 6-7:2-4:
1.
4. The platinum-cured high-temperature resistant and high-flame-retardant silicone rubber according to claim 3, characterized in that, The modified aluminum hydroxide was prepared by the following method: 1) Mix aluminum hydroxide and 3,4-dihydroxybenzoic acid solution, grind, and filter to obtain activated aluminum hydroxide; 2) Dissolve hexachlorocyclotriphosphazene in petroleum ether to obtain an epoxy phosphate-petroleum ether solution. Then, under stirring conditions, add active aluminum hydroxide to the epoxy phosphate-petroleum ether solution, heat to 55-70℃, add triethylamine dropwise, react for 0.5-2 hours, filter to obtain filter cake, wash and dry to obtain modified aluminum hydroxide.
5. The platinum-cured high-temperature resistant and high-flame-retardant silicone rubber according to claim 4, characterized in that: The ratio of aluminum hydroxide, 3,4-dihydroxybenzoic acid solution, hexachlorocyclotriphosphazene, petroleum ether and triethylamine is 10-15g:10-20ml:4-5-5g:60-80ml:1g.
6. The platinum-cured high-temperature resistant and high-flame-retardant silicone rubber according to claim 3, characterized in that: The modified silicon micro powder is obtained by mixing silicon micro powder and mercaptosilane coupling agent in a weight ratio of 10:0.5-1.
7. The platinum-cured high-temperature resistant and high-flame-retardant silicone rubber according to claim 1, characterized in that: The hydrogen-containing crosslinking agent is composed of side-chain hydrogen-containing silicone oil with a hydrogen content of 0.3%-0.75% and methyl low-hydrogen silicone oil with a hydrogen content of 0.5%-1.0% in a weight ratio of 3:0.5-1.
5.
8. The platinum-cured high-temperature resistant and high-flame-retardant silicone rubber according to claim 1, characterized in that: The structure control agent includes at least one of diphenylsilanediol, dimethyldimethoxysilane, methylphenyldimethoxysilane, and hexamethyldisilazane.
9. The platinum-cured high-temperature resistant and high-flame-retardant silicone rubber according to claim 1, characterized in that: The methyl vinyl silicone rubber raw rubber has a vinyl content of 0.20%-0.30% and a molecular weight of 400,000-600,000.
10. A method for preparing platinum-cured high-temperature resistant and high-flame-retardant silicone rubber as described in any one of claims 1-9, characterized in that, The preparation steps include the following: S1. Knead the raw methyl vinyl silicone rubber. During the kneading process, add highly hydrophobic modified fumed silica, silane interface compatibilizer, hydroxyl silicone oil and structure control agent in sequence. After the addition is completed, continue kneading for 180-200 min. Then add halogen-free flame retardant filler, composite high temperature resistant stabilizer and hydrogen-containing crosslinking agent. After the addition is completed, continue kneading for 45-60 min to obtain a mixture. S2. Reduce the temperature of the mixture to below 35°C, add the inhibitor first, then add the platinum vulcanizing agent, mix evenly, roll and pass through thin sheets, vulcanize, and obtain platinum vulcanized high temperature resistant and high flame retardant silicone rubber.